Study of semen production of sire's Holstein breed - Shamshidin, Alzhan; Alshinbaev, Orinbasar; Rakhimzhanova, Damegul; Mussabekov, Aidos (Scientific Journal of Zoology, 2017)
The differences of sperm productivity of bulls of Holstein breed are found, and correlation and regression analysis between the main quantitative and qualitative indicators of sperm productivity of bulls is done. The morphological, biochemical and physiological indicators of sperm and blood of bulls are studied and their connection with reproductive capacity of the bulls of Holstein breed is found. Biochemical studies of enzyme activity of succinate dehydrogenase, lactate dehydrogenase, alkaline and acid phosphates in sperm of bulls are done and the relationship of enzyme activity with main indicators of sperm productivity is found. The morphological characteristics of sperm and blood of bulls of Holstein breed are studied, as well as their relationship with the main indicators of sperm production.